Entre a realidade e a Ilusão do Ensino Remoto em Moçambique – perceções e contextos. caso da Universidade Licungo - (:unkn) unknown (Universidade Federal do Amazonas, 2023)
With the emergence of COVID-19, at the end of 2019, and its proliferation in 2020, difficulties arose in adapting to the 'new normal' in several sectors, including education, which demanded both students and teachers and of the entire school community adaptations for the new teaching modality, Remote Learning. Linked to our experiences, experiences and the fact that Digital Technologies have been taking their place in the world, we asked in this research: How initial and continued teacher training could reduce the impact of remote action situations experienced during the recent international health emergency 2020-2021? In this direction, the present research, carried out under the Doctorate in Education at PPGE/UFAM, aims in a general way to describe characteristics of installed infrastructures associated with teaching-study mediated by Digital Platforms of online learning at Licungo University, as an educational response to the international health emergency 2020-2021(COVID-19), associated with the need for curricular adjustments in the initial and continuing training of teachers. With a qualitative approach, the research in question is guided by a Case Study, with students from the Licungo University in Mozambique as participants. Thus, we adopted as instruments for collecting information the questionnaire prepared and made available by the digital platform Google Forms whose link was sent by Email and WhatsApp, and the semi-structured interview. We used our own questionnaires composed of open and closed questions, which were answered anonymously and voluntarily by 53 students from the Licungo University - Extension of Beira distributed in 3 sections namely: I) Identification and context; II) Information on the teaching and learning process during the period 2020-2021 III) Information on the academic performance of students during the international health emergency. The interview was carried out by the Google Meet platform with 3 students from the same University. The results showed that, in the students' perception, teachers have weaknesses in terms of teaching skills through digital platforms, so much so that the form of interaction most used by teachers was WhatsApp, which is not necessarily an educational platform. Digital Platforms provide support to the teaching-study-learning process, not only for access to content, but also for teacher-student interaction and group work and, when used correctly, for continuity of face-to-face work. The research showed that in the context of Mozambique, remote teaching has imposed new challenges for HEIs, since students suffer from the lack of preparation to deal with Digital Platforms and in their perception, teachers face the same difficulties. Hence, these weaknesses influenced the performance of students and suggest that there is a need to strengthen planning for technological updating of school infrastructure through continuous investments to optimize the teaching-study-learning process in a broad sense, including the use of existing digital technologies.
Keywords: Ensino via Web; Ensino auxiliado por computador; Tecnologia educacional; Realidade virtual no ensino superior - Moçambique; CIENCIAS HUMANAS: EDUCACAO; Tecnologias Digitais; Ensino e Estudo Remotos; Plataformas Digitais; Google for Education; Ensino Superior em Moçambique